2022
DOI: 10.1080/21655979.2022.2074108
|View full text |Cite
|
Sign up to set email alerts
|

A high level of the long non-coding RNA MCF2L-AS1 is associated with poor prognosis in breast cancer and MCF2L-AS1 activates YAP transcriptional activity to enhance breast cancer proliferation and metastasis

Abstract: Breast cancer (BC) is one of the most prevalent gynecologic malignant tumors with a poor prognosis and the second leading cause of cancer-related deaths in women worldwide. In recent years, it has been shown that long non-coding RNA (lncRNA) plays an important role in the development of breast cancer (BC). An antisense lncRNA from the MCF2 cell line (MCF2L-AS1) has been discovered recently and has been shown to function in a variety of malignancies. However, its function as a regulator of BC development has ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…SORBS1 acts as a potential suppressor in tumorigenesis and low levels of the gene enhances the invasive ability of BRCA cells through activation of c-Jun N-terminal kinase (JNK) (Song et al, 2017). ADAMTSL5 loci is targeted by estrogen receptor alpha (ERα) ( Zhang et al, 2021 ), while MCF2L Antisense RNA 1 promotes the transcriptional activity of yes-associated protein (YAP) to enhance the proliferation and metastasis in Breast cancer ( She et al, 2022 ). LRP5 activity associated with the β-catenin signaling pathway in breast cancer is reported in the literature ( Björklund et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…SORBS1 acts as a potential suppressor in tumorigenesis and low levels of the gene enhances the invasive ability of BRCA cells through activation of c-Jun N-terminal kinase (JNK) (Song et al, 2017). ADAMTSL5 loci is targeted by estrogen receptor alpha (ERα) ( Zhang et al, 2021 ), while MCF2L Antisense RNA 1 promotes the transcriptional activity of yes-associated protein (YAP) to enhance the proliferation and metastasis in Breast cancer ( She et al, 2022 ). LRP5 activity associated with the β-catenin signaling pathway in breast cancer is reported in the literature ( Björklund et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…A series of metastasis-related long non-coding RNA (MRLNRs) have been identified to regulate the metastatic processes of various tumors. The high expression of lncR-MCF2L-AS1A in breast tumor cells promotes metastasis by increasing YAP transcription [ 14 ]. In addition, Dong et al found a positively modulating relationship between lncR-TRIM28-14 and COL4A1 in the peritoneal metastatic tissues of gastric cancer, indicating the potential role of lncR-TRIM28-14 in metastatic evaluation and strategy [ 15 ].…”
Section: Introductionmentioning
confidence: 99%